Desindustrialização no Brasil: um debate dos anos 2000 - Prado, Altevir Dias do (Universidade do Vale do Rio dos Sinos, 2014)
This dissertation aims to present a discussion of deindustrialization in Brazil in the 2000s. Whereas the industry has a high potential to leverage economic growth and development, especially in terms of technological advance, deindustrialization can be an important threat to the Brazilian economy. Firstly, we seek to highlight the importance of industrialization in the economic development process, emphasizing the perspective of linking innovation, productivity and foreign market. Following, we present the theoretical concept of what deindustrialization is, natural and early in the light of the main exponents who studies the subject in the world. Afterwards we presented a brief history of how the process of industrialization was in Brazil in order to subsidize the discussion of deindustrialization in a contextualized way. Following, we appeal to the main authors who have already studied the phenomenon in the Brazilian economy presenting various existing positions for and against the claims that Brazil is undergoing deindustrialization process. Finally, we make a review of the data seeking to answer the question under the perspective of employment, added value, productivity, investment, per capita income and foreign trade, appealing to historical series of official sources.
Keywords: Industrialização; Desindustrialização; Crescimento; Desenvolvimento; Industrialization; Deindustrialization; Growth; Development; ACCNPQ::Ciências Sociais Aplicadas::Economia